Search costs in concentrated markets: An experimental analysis - Claudia Möllers; Torben Stühmeier; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
This paper experimentally studies the role of search cost in duopoly markets where sellers may be able to coordinate pricing decisions. We vary the level of search cost and whether sellers can communicate. While we find that consumers are more likely to invest in search when cost is reduced, we find that a reduction of search cost does not influence prices. This effect is not influenced by the availability of seller communication. Our results suggest that policy interventions that aim to increase the competitiveness of markets via reducing search cost may not be effective in concentrated markets.
Keywords: K23; L13; L51; 330; Search; Collusion; Regulation